2008
DOI: 10.1371/journal.pone.0002319
|View full text |Cite
|
Sign up to set email alerts
|

Heparanase Facilitates Cell Adhesion and Spreading by Clustering of Cell Surface Heparan Sulfate Proteoglycans

Abstract: Heparanase is a heparan sulfate (HS) degrading endoglycosidase participating in extracellular matrix degradation and remodeling. Apart of its well characterized enzymatic activity, heparanase was noted to exert also enzymatic-independent functions. Non-enzymatic activities of heparanase include enhanced adhesion of tumor-derived cells and primary T-cells. Attempting to identify functional domains of heparanase that would serve as targets for drug development, we have identified heparin binding domains of hepar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
100
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 98 publications
(105 citation statements)
references
References 58 publications
5
100
0
Order By: Relevance
“…One possibility is that heparanase, which is known to have multiple heparan sulfate-binding motifs, binds to the cell surface heparan sulfate proteoglycan syndecan-1, triggers clustering of syndecan-1 with the insulin receptor, and induces its dimerization and autophosphorylation. A previous study has shown that heparanase can induce the clustering of syndecan-1, thereby initiating signaling cascades that involve Rac1, Src, and the PKC pathways, resulting in enhanced cell adhesion and spreading (38). Similar to this finding, we also observed high PKC activity in heparanase-high cells and have found that heparanase-high cells spread much more avidly than do heparanase-low cells.…”
Section: Discussionsupporting
confidence: 89%
“…One possibility is that heparanase, which is known to have multiple heparan sulfate-binding motifs, binds to the cell surface heparan sulfate proteoglycan syndecan-1, triggers clustering of syndecan-1 with the insulin receptor, and induces its dimerization and autophosphorylation. A previous study has shown that heparanase can induce the clustering of syndecan-1, thereby initiating signaling cascades that involve Rac1, Src, and the PKC pathways, resulting in enhanced cell adhesion and spreading (38). Similar to this finding, we also observed high PKC activity in heparanase-high cells and have found that heparanase-high cells spread much more avidly than do heparanase-low cells.…”
Section: Discussionsupporting
confidence: 89%
“…In U87 MG human glioma cells, clustering of syndecan-4 by latent heparanase or an antiheparanase antibody was sufficient to induce cell spreading, a process involving PKC activation. 17 In addition, on binding of phosphatidylinositol 4,5-bisphosphate (PtdIns(4,5P)(2)) to its cytoplasmic domain, oligomerization of syndecan-4 was promoted with a subsequent upregulation of PKCα. 42,43 In this study, it is likely that clustering of syndecan-4 with latent heparanase triggers RhoA activation.…”
Section: Discussionmentioning
confidence: 99%
“…Immunocytochemistry-Immunofluorescent staining was performed essentially as described (21,30,31). Staining was observed under a fluorescent confocal microscope.…”
Section: Methodsmentioning
confidence: 99%